Penerapan Model Cooperative Learning Tipe Picture And Picture Berbantuan Media Flash Card Untuk Meningkatkan Kosakata Bahasa Inggris Siswa Sekolah Dasar - Neneng Sri Wulan; Hisny Fajrussalam; Nihlatul Hayyati (Al Qodiri : Jurnal Pendidikan, Sosial dan Keagamaan, 2023)
The use of English is something that must be present in a learning that is integrated into every other activity. English is very important to learn, because to communicate between nations, because English is an international language. Mastery of vocabulary is the most important part of being able to communicate fluently. This research was motivated by the lack of teaching staff at the school to teach English language learning, then about the quality of students who are still low in English vocabulary, and limited teaching aids or learning media. This research was carried out at SD Negeri 1 Pesanggrahan with the subject of 21 students. The aim of this research is to improve teacher and student activities and English vocabulary skills with a picture and picture type cooperative learning model with the help of flash card media. The type of research used is classroom action research. The results of the study showed an increase in teacher and student activity, as well as English vocabulary skills. Based on the acquisition of the first cycle, the average acquisition of students' English vocabulary skills was 70.00% in the good category, there were 16 students exceeding KKM 70. In the second cycle, the average English vocabulary ability of students was 83.80% with a very good category, there were 19 students exceeding KKM 70. With this, the learning model in this study was successful. Keyword: English Language Learning, Vocabulary Skills, Picture and Picture Cooperative Learning Model